KONFLIK HUKUM LEGALITAS PERKAWINAN BEDA AGAMA DI INDONESIA - Hasna Lathifatul Alifa; Ali Sodiqin; Bian Ambarayadi (Justicia Islamica, 2023)
This article explores legal conflicts regarding the legality of interfaith marriages in Indonesia. There was a legal conflict between the provisions in Article 2 paragraph (1) of Law No. 1 of 1974 concerning Marriage, which determines the validity of marriages based on religious law, with Articles 34 and 35 of Law No. 23 of 2006 concerning Citizenship Administration, which states that a valid marriage is reported and registered. Article 35, letter (a) says that the court determines a legal marriage. Disharmony of laws and regulations concerning interfaith marriage regulations has influenced the interpretation of legal provisions, resulting in differences in judges' decisions. This raises the question of harmonizing the legal provisions between these laws and regulations. Analysis of the problem of the legality of interfaith marriage law is carried out using a normative juridical approach by using Soerjono Soekanto's theory of legal effectiveness. The results of this study indicate that the disharmony of interfaith marriage law causes multiple interpretations for judges in determining the legality of interfaith marriages. Unclear regulations cause the legal rules of interfaith marriages in Indonesia to cause conflicts between legal institutions. The legal substance factor is the main root of the ineffectiveness of the regulations on interfaith marriages in Indonesia. Disharmony between legal authorities impacts conflicts between legal institutions and influences the practice of interfaith marriages in society.